Higher Education in Challenging Times: Modes of Lifelong Learning Provision and the Case of Islamic Education - Isanović Hadžiomerović, Amina (Context: Journal of Interdisciplinary Studies, 2022)
Growing insecurity in contemporary society has helped make lifelong learning a prominent feature of postmodern discourses on education and society. As an independent discourse, lifelong learning has generated diversified learning contexts and a proliferation of education provision, issuing a serious challenge to traditional formal and institutional models of education. As a result, higher education, long enclosed in an ivory tower of elitist scholarship and accessible to only a few privileged individuals, has started to change course and open up to non-traditional disciplines, learners, and students. The trend to massification has pushed it to embrace students of various backgrounds and levels of academic preparedness. Policies have been created that facilitate implementation of higher education’s “lifelong dimension”, just as models have been designed that fit programs ranging from vocational to liberal education. This paper applies this framework to examine models for incorporating lifelong learning provision into Islamic education at tertiary level. Concluding remarks stress the significance of lifelong learning opportunities in Islamic education, especially given current demand for higher education as a way to meet the diverse needs of society and the public promptly.